The Effect of Eco Efficiency, Number of Audit Committees and Sustainability Report on Going Concern Audit Opinion - Putra, Andika Eka; Saputra, Dian (GoAcademica Research & Publishing, 2024)
Going concern for business is always a major issue that is considered by the management. The going concern audit opinion is one of the elements that displays the findings of the business continuity assessment. It can provide credibility that will affect investors' confidence in investing, and provide guarantees for companies that have potential issues related to their going concern. The goal of this study was to investigate how going concern audit opinion was impacted by eco-efficiency, the number of audit committees, and sustainability reports. Based on mining companies listed between 2020 and 2022 on the Indonesia Stock Exchange (IDX), the research was conducted. This study makes use of secondary data in the form of financial statements. Structural Equation Modeling - Partial Least Square (SEM-PLS) is the data analysis method used. The findings demonstrated that going concern audit opinions are significantly impacted by eco efficiency, the number of audit committees, and sustainability reports.